Avaliação da implementação da política nacional de resíduos sólidos em municípios goianos - Silva, Artur Candido Barbosa (2017)
The implementation evaluation of public policies aims to understand the paths taken, the obtained results, and subsidizes the decision making related to the adjustment, maintenance or exclusion of actions employed in support objectives predefined. This research had as its central objective the implementation process evaluation, taking as object of study the National Solid Waste Policy (NSWP). As specific objectives, it was proposed to (i) verify in the municipalities what and how the activities were or are being developed, (ii) identify factors that facilitate and impede the implementation of NSWP in the cities surveyed, and (iii) identify, in light of the NSWP objectives, the level of implementation of this policy in the studied municipalities. The methodology used was exploratory and descriptive, with mixed design, using multiple cases referring to the following goianos municipalities (Goiânia, Aparecida de Goiânia, Senador Canedo and Mossâmedes), and interviews were conducted together with those responsible for NSWP in each city. The level of implementation of NSWP policies were classified as: implemented, partially implemented, planned and not implemented. It could be concluded that the implementation of NSWP is on progresses in a big part of the cities surveyed, and it could also be seen that the population level of the municipalities were not representative to define the level of a consistent implementation. It was verified two extremes related to the implementation, Goiânia (the most populous) and Mossâmedes (the less populous). While an intermediate-sized municipality remains "in planning". Although the shortage of resource for implementation has been recurrent among all municipalities surveyed, and was considered as a factor that restricts the implementation actions. It was evidenced that the lack of money is not the only problem, but rather, the lack of will and prioritization of public management for actions aimed to the environmental preservation and integrated solid waste management.